The impact of anthropogenic activities on heavy metal (Cd, Cu, Ph and Zn) pollution: Comparison of the metal levels in the green-lipped mussel perna viridis (Linnaeus) and in the sediment from a high activity site at Kg. Pasir Puteh and a relatively low activity site at Pasir Panjang - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan; A., Rahim Ismail (Universiti Putra Malaysia Press, 2004)
It has been a common practice to select different environmental backgrounds in biomonitoring studies of heavy metal contamination (Yap et al. 2002a; 2002b; 2003a; 2003b). It is expected to obtain different pollutant concentrations in a selected biomonitoring agent. An interesting question that may arise here is 'Are all heavy metal levels high in a known high human activity sampling site ?' This question comes to mind since most researchers would assume a positive answer while ecotoxicologists would like to know which metal(s) is(are) high (maybe not all heavy metals) at that sampling site. The environmental background is closely related to the description of the sampling site which can range from an uncontaminated or pristine site to a highly contaminated site that is known to receive a lot of anthropogenic inputs.